MSME Export Performance: Do Trade Barriers Matter? - Jenifer; Dr. Reena (Srusti Management Review, 2025)
Emerging markets depend on MSMEs for innovation and job generation. Despite their prominence, trade policies impact these companies’ export potential. These policies have pros and cons, including free trade agreements and government assistance, but also high tariffs and complicated regulations. Understanding how trade policies affect MSME export capacities is crucial to their growth and global competitiveness. The main aim of this research is to determine the most critical trade barriers perceived by MSMEs and measure their contribution to export performance. The research also assesses how market conditions and trade policy influence the success of MSMEs in overseas markets. A formal questionnaire was administered to 394 MSMEs involved in exporting to emerging markets. Data dimension reduction and bundling trade barriers into dominant factors were accomplished through factor analysis. Chi-square tests were utilized to investigate the correlation between identified factors and export performance. Market Access, Market Entry Barriers, Infrastructure Limitations, Regulatory Constraints, External Barriers and Operational Trajectory were the key trade barriers identified from the research. These barriers collectively hinder export activities. However, the Chi-square tests demonstrated an insignificant association between the trade barriers faced by MSMEs and their export performance.